2023
DOI: 10.1111/ajae.12419
|View full text |Cite
|
Sign up to set email alerts
|

Information acquisition and the adoption of improved crop varieties

Abstract: Inadequate information on the benefits of and knowledge about innovative agricultural technologies continue to be a major constraint to technology adoption among smallholder farmers in developing countries. The low adoption of new technologies is one of the causes of low productivity and high poverty incidence among smallholder farmers, particularly in Africa. In this paper, I briefly review the literature on social networks and technology diffusion, and argue that the diffusion potential of social networks is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…, 2021; Che et al. , 2022; Abdulai, 2023), we measure peer effect by the average share of SAAs, using farm households except for the household under consideration ( n −1), in a given community. We compute peer effects as n /( m −1), where n represents the number of a farmer's peers using SAAs in the given community, and m represents the total number of households surveyed in that community.…”
Section: Empirical Specificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2021; Che et al. , 2022; Abdulai, 2023), we measure peer effect by the average share of SAAs, using farm households except for the household under consideration ( n −1), in a given community. We compute peer effects as n /( m −1), where n represents the number of a farmer's peers using SAAs in the given community, and m represents the total number of households surveyed in that community.…”
Section: Empirical Specificationsmentioning
confidence: 99%
“…According to peer effect theory (Sampson and Perry, 2018), an individual's behavior is affected by their peer's behavior. Following previous studies (Steinh€ ubel et al, 2020;Kolady et al, 2021;Che et al, 2022;Abdulai, 2023), we measure peer effect by the average share of SAAs, using farm households except for the household under consideration (nÀ1), in a given community. We compute peer effects as n/(mÀ1), where n represents the number of a farmer's peers using SAAs in the given community, and m represents the total number of households surveyed in that community.…”
Section: Modeling the Impact Of Saas Use On Land Transfer-in Areamentioning
confidence: 99%
See 1 more Smart Citation
“…This provides them with different information and knowledge to feed their requirements [48][49][50]. Studies have shown that both quantity (number of information sources) and quality of information influence the adoption of new technologies and sustainable agricultural practices [51][52][53].…”
Section: The Impact Of Information Acquisition Ability On Farmers' He...mentioning
confidence: 99%
“…Among the many factors contributing to food insecurity, malnutrition, and low socio-economic index among rural farmers are inadequate farm inputs, low irrigation, climate change, land degradation, and obsolete planting methods [19]. Additionally, the cultivation of underperforming cultivars due to the lack of access to superior varieties exacerbates these challenges [20,21]. However, an often underestimated yet significant factor limiting yields on A. hybridus farms is the inadvertent mixing of seeds from different varieties, each with different yield capacities.…”
Section: Introductionmentioning
confidence: 99%